Unraveling the salt tolerance of Phi29 DNA polymerase using compartmentalized self-replication and microfluidics platform - Sun, Yaping; Ko, Danny Hsu; Gao, Jie; Fu, Kang; Gao, Yaping; Zhang, Qiwen; Baldi, Salem; Hong, Tao; Ivanov, Igor; He, Yun; Tian, Hui (Frontiers in Microbiology, 2023)
In Phi29-α–hemolysin (α-HL) nanopore sequencing systems, a strong electrochemical signal is dependent on a high concentration of salt. However, high salt concentrations adversely affect polymerase activity. Sequencing by synthesis (SBS) requires the use of phi29 polymerase without exonuclease activity to prevent the degradation of modified nucleotide tags; however, the lack of exonuclease activity also affects polymerase processivity. This study aimed to optimize phi29 polymerase for improved salt tolerance and processivity while maintaining its lack of exonuclease activity to meet the requirements of nanopore sequencing. Using salt tolerance compartmentalized self-replication (stCSR) and a microfluidic platform, we obtained 11 mutant sites with enhanced salt tolerance attributes. Sequencing and biochemical analyses revealed that the substitution of conserved amino acids such as G197D, Y369E, T372N, and I378R plays a critical role in maintaining the processivity of exonuclease-deficient phi29 polymerase under high salt conditions. Furthermore, Y369E and T372N have been identified as important determinants of DNA polymerase binding affinity. This study provides insights into optimizing polymerase processability under high-salt conditions for real-time polymerase nanopore sequencing, paving the way for improved performance and applications in nanopore sequencing technologies.